1991
DOI: 10.1021/jm00115a001
|View full text |Cite
|
Sign up to set email alerts
|

Structure activity studies related to 2-(3,4-dichlorophenyl)-N-methyl-N-[2-(1-pyrrolidinyl)-1-substituted-ethyl]acetamides: a novel series of potent and selective .kappa.-opioid agonists

Abstract: This paper describes the synthesis of a series of N-[2-(1-pyrrolidinyl)ethyl]acetamides 1, variously substituted at the carbon adjacent to the amide nitrogen (C1), and related analogues, together with their biological evaluation as opioid kappa agonists. In the first part of the study, the variants in N-acyl, N-alkyl, and amino functions were explored when the substituent at C1 was 1-methylethyl and the optimum was found to be exemplified by 2-(3,4-dichlorophenyl)-N-methyl-N-[(1S)-1-(1-methylethyl)-2- (1-pyrro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 3 publications
2
29
0
1
Order By: Relevance
“…Conformational Space of κ -Agonists. Although the key structural features of U50,488 derivatives have been identified by SAR (Figure ), the conformational preferences of the free ligand or that involved in the receptor−ligand complex have not been investigated in detail. , In addition, the dynamic nature of the structure is of additional interest since there are many freely rotatable bonds in each molecule.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conformational Space of κ -Agonists. Although the key structural features of U50,488 derivatives have been identified by SAR (Figure ), the conformational preferences of the free ligand or that involved in the receptor−ligand complex have not been investigated in detail. , In addition, the dynamic nature of the structure is of additional interest since there are many freely rotatable bonds in each molecule.
…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, some insights on the formation of 1 − 10 can be obtained from the structure−activity relationship (SAR) data for this ligand series. By varying the aryl ( 1 vs 2 ) , and amide ( 1 vs 9 , 10 ) substituents, altering the chain length (spacer) between the aryl and amide group, modifying the cyclohexyl moiety ( 1 vs 3 − 8 ), and changing the ring size that contains the tertiary nitrogen, SAR studies have identified various means of optimizing the receptor−ligand interaction to improve the κ-opioid receptor binding and selectivity. , Although a simple spirotetrahydrofuranyl substituent on the cyclohexane ring in U50,488 [ K i ( 1 ) = 0.9 nM] reveals an increased ligand binding [ K i ( 4 ) = 0.3 nM],15b dramatic effects in the μ/κ-selectivity are observed when the aryl group is modified in concert . Thus, CI-977 ( 5 ) displays greater selectivity (1575-fold) 7 for the κ-receptor as compared to 1 and 4 (280-fold) 15b.…”
Section: Introductionmentioning
confidence: 99%
“…The first example of these compounds is U50488 (84) that has 50-fold selectivity for k receptor over m receptor. 159 Other agonists belonging to this class are U69593 (85), 160 PD117302 (86), 161,162 CI977 (enadoline (87)), 163,164 GR-89696 (88), [165][166][167] piperidine analogues (89) of GR-89696, 168,169 and pyrrolidinyl ethylacetamide derivatives (90,91), 170 all of which show high affinity and selectivity for k receptor over m and d receptors. A morphinan derivative, TRK-820 (92), exhibits high potency and k selectivity over m and d receptors.…”
Section: K-selective Agonists and Antagonistsmentioning
confidence: 99%
“…Ïðè ýòîì ñàìûì ýôôåêòèâíûì îêàçàëîñü âå-ùåñòâî ïîä ëàáîðàòîðíûì øèôðîì ICI 199,441 (ðèñ. 6), êîòîðîå ïî ñåëåêòèâíîñòè ê k-ðåöåïòîðàì â 146 ðàç ïðåâîñõîäèëî U50,488 íà ìîäåëÿõ in vitro è ïðîÿâëÿëî âûðàaeåííîå íàëîêñîíîáðàòèìîå àíàëüãåòè-÷åñêîå äåéñòâèå â òåñòå óêñóñíûõ êîð÷åé (ÝÄ 50 = 0,004 ìã/êã ïîäêîaeíî) [78]. Êðîìå òîãî, áûëà ïîêàçàíà âûñîêàÿ ýôôåêòèâíîñòü ICI 199,441 â óñëîâèÿõ ôîðìà-ëèíîâîé ãèïåðàëüãåçèè, à òàêaeå ïðè íåéðîïàòè÷åñêîé áîëè, èíäóöèðîâàííîé ïåðåâÿçêîé ñåäàëèùíîãî íåðâà [16,79].…”
Section: òðàíñ-2-(34-äèõëîðôåíèë)-n-ìåòèë-n-unclassified